An assessment of indigenous knowledge of apitherapy in the Oromia region, Ethiopia - Meseret Gemeda; Deressa Kebebe; Teferi Demto (Open Journal of Biological Sciences - Peertechz Publications, 2022)
Apitherapy is the use of bee products such as honey, pollen, propolis, royal jelly, bee venom, and wax is used to prevent or treat illness and promote healing. The objectives of this study are to assess and document indigenous knowledge on the medicinal values of bee products in Ethiopia and generate baseline information on indigenous practices of the medicinal value of beehive products for further study. This study was conducted in beekeeping potential areas of Oromia Regional state by selecting seven zones and from each zone two districts and a total of 14 districts (Woreda) based on their potential for beekeeping, the existence of long-aged bee-keepers and accessibility. using a purposive sampling method and questionnaires were distributed to the elders and well-known traditional healers of the study areas. In answering the questionnaires 22-100 ages dwellers or respondents participated. The survey was conducted in 7 zones namely Jimma, Ilu ababora, West wollega, East wollega, East Shoa, West shoa, and Buno Bedele. Simple descriptive statistics were used to analyze the data obtained by collected questionnaires. The result of the study showed that 49.3% of Apis mellifera honey and 31.9% of stingless bee honey, majorly used bee products for apitherapy, and 70.3 % of the bee products used using traditional collection method. According to this study's results, the traditional drug was prepared from honey in liquid form which comprises the biggest portion mark of 63.4% of respondents. The majority of the respondents strongly agree with bee products as a treatment for different diseases such as asthma, cough, common cold, TB, and wounds. A major challenge faced during using of bee products as medicine is the absence of awareness of apitherapy as it was reported by 28.8%. of the respondents. Thus, it can be concluded that bee products are well-known apitherapy in the Oromia region and it was recommended that awareness creation of bee products as apitherapy and further research on the medicinal value of beehive products for confirmation as medicine for different diseases since it may be a solution for various diseases resisting modern drugs.